Tracing the legacy: Li Jinhui’s influence on Chinese early childhood music education and the evolution of kindergarten music teaching materials - Loo, Fung Chiat; Huang, Yi (Universitat Jaume I, 2024)
Background: Early 20th century China marked the inception of music education in early childhood. This field and Chinese early childhood curriculum have evolved substantially over the past century. Since the early 21st century, music education in China has become a vital tool for improving early childhood music literacy and promoting overall child development. Li Jinhui (1891–1967) is acknowledged as the father of Chinese children’s song and dance dramas (儿童歌舞剧) and popular music. His works span literature, drama, education, music, and dance. In the late 1920s, Li’s pop music works faced criticism of the alleged pornographic content. The Ministry of Education banned this work since1930. Despite the late 20th-century lifting of the prohibition and increased scholarly interest in his works, research has predominantly focused on pop music and literary contributions. Thus, his substantial influence on early childhood music education has been neglected. Methodology & Result: This study investigates Li’s three compositions from 1920 to 1930 and his 1933 kindergarten music teaching materials, aiming to determine his impact on later composers and contributions to children’s music composition. In addition, we analyzed kindergarten music teaching materials from 1983 by the Chinese Ministry of Education, the objective of which was to examine their influence and evolution. This study employed a qualitative approach, concentrating on biographical and music analysis approach. Primary data sources included document analysis and interviews, using text analysis of scores, documents, and transcripts. This study identified three modern music compositions influenced by Li’s work. In addition, the Ministry of Education’s childhood music teaching materials from 1983 were found to reference Li’s 1933 childhood teaching materials. Conclusion: Li’s work has profoundly influenced children’s compositions and contemporary music in China. These findings reevaluate his contributions and teaching resources in contemporary early childhood music education.